Comparison between protocols for the determination of anaerobic threshold in adolescent swimmers - Melo Altimari, J.; Altimari, L. R.; Coelho Greco, C. [UNESP]; Yuzo Nakamura, F.; Serpeloni Cyrino, E.; Traina Chacon-Mikahil, M. P. (My University, 2010)
Aim. The purpose of this study was to compare the anaerobic threshold speed (AT) obtained from fixed lactate blood concentrations (AT 4 mM and AT 3.5 mM), lactate minimum speed (LM) and critical speed (CS), determined from different distances in fifteen Brazilian national level swimmers (10 boys = 14.8 ± 0.6 years old and 5 girls = 14.6 ±0.8 year-old). Methods. The tests to determine the AT 4 mM, AT 3.5 mM, LM and CS were performed in a 25 m swimming pool and consisted of 7 or 8 evaluations separated by 24-48 h intervals. Data were submitted to analysis of variance (ANOVA) for repeated measures, followed by the post hoc Scheffé test and Pearson correlation coefficients. Significance was set at P<0.01. Results. There were no significant differences among the values for AT 4 mM and CS1 (1.34 ± 0.05 vs. 1.33 ± 0.05 m.s -1, respectively). However, AT 4 mM and CS1 were significantly higher than AT 3.5 mM (1.28 ± 0.04 m.s -1), LM (1.27 ± 0.05 m.s -1), CS2 (1.26 ± 0.06 m.s -1), CS3 (1.27 ± 0.06 m.s -1) and CS4 (1.25 ± 0.07 m.s -1). There were no significant differences among the values for AT 3.5 mM, LM, CS2, CS3 and CS4. Conclusion. The results obtained in this study suggest that the anaerobic threshold determined by a fixed lactate concentration of 3.5 mM, as well as the LM and the CS methods determined by different distances, seem to be the most appropriate indexes for the evaluation of aerobic capacity in adolescent swimmers.
Keywords: Adolescents; Anaerobic threshold; Sodium lactate; Swimming; lactic acid; adolescent; aerobic capacity; anaerobic threshold; Brazil; critical speed; female; human; intermethod comparison; lactate blood level; lactate minimum speed; male; normal human; swimming; training; validity; velocity